PERAN MEDIASI DIGITAL MARKETING PADA PENGARUH LITERASI DIGITAL DAN INOVASI PRODUK TERHADAP KINERJA UMKM - Yanti, Ni Putu Yayuk Puspita; Telagawathi, Ni Luh Wayan Sayang; Widiastini, Ni Made Ary (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024DO - 10.24843/EEB.2024.v13.i02.p08, 2024)
This research aims to analyze the influence of digital marketing in mediating digital literacy and product innovation on the performance of MSMEs assisted by the Udayana University Business Incubator using Resource Based View (RBV) as a theoretical basis for analyzing the relationship between these variables. The sample used in this research was 100 respondents from MSMEs assisted by the Udayana University Business Incubator. The data analysis technique used is SEM-PLS. The results show that digital literacy and product innovation have no significant effect on MSME performance, digital marketing has a significant effect on MSME performance, digital literacy and product innovation have a significant effect on digital marketing, digital marketing provides a perfect mediating effect on the influence of digital literacy on MSME performance, and digital marketing provides a partial mediating effect on the influence of product innovation on the performance of MSMEs assisted by the Udayana University Business Incubator. It is hoped that these findings will provide an empirical contribution to management science, especially the performance of MSMEs and will be useful for the Udayana University Business Incubator in carrying out coaching patterns related to digital literacy, product innovation and digital marketing in order to improve the performance of MSMEs.